A CCA-secure multi-conditional proxy broadcast re-encryption scheme for cloud storage system. (August 2019) - Liu, Yepeng; Ren, Yongjun; Ge, Chunpeng; Xia, Jinyue; Wang, Qirun
Abstract: Conditional proxy re-encryption allows a semi-trusted third-party proxy to convert Alice's ciphertext that meets a certain condition into another set of ciphertext. Meanwhile, the proxy cannot obtain any valuable information in the process. Nevertheless, a single re-encryption condition is difficult to meet the needs of practical applications, and the existing conditional proxy re-encryption scheme cannot flexibly control the conversion conditions. To solve this problem, this paper proposes a multi-conditional proxy broadcast re-encryption (MC-PBRE) scheme for file sharing systems. In our scheme, a single user can delegate the decryption rights of the encrypted file to a group of users. At the same time, users can set any number of conditions to control the user group decryption permissions. This paper demonstrates the security of the scheme for chosen-ciphertext attacks in the standard model. Furthermore, the program can resist collusion attacks, which means that the agent cannot collude with the user group to get the private key of the principal.